Clinical Significance of Metastasis or Micrometastasis to the Lymph Node Along the Superior Mesenteric Vein in Gastric Carcinoma: A Retrospective Analysis - Xu, Xing; Zheng, Guoliang; Zhang, Tao; Zhao, Yan; Zheng, Zhichao (Frontiers in Oncology, 2021)
Background: The validity of lymphadenectomy of the lymph node along the superior mesenteric vein (LN14v) in gastric cancer remains controversial. The study investigated the characteristics and prognosis of gastric cancer with metastasis or micrometastasis to LN14v. Methods: A retrospective study of 626 patients undergoing radical gastrectomy in our center from January 2003 to December 2015 was analyzed. In total, 303 patients had lymphadenectomy of LN14v, and lymph node micrometastasis was evaluated by immunohistochemical staining for cytokeratin nodes CK8/18. A logistic regression model was applied to confirm the predictive factors of micrometastasis. Survival analysis was performed to evaluate the effect of micrometastasis or metastasis on prognosis. Results：The metastatic rate of the LN14v lymph node was 15.8% and the micrometastatic rate was 3.3%. Multivariate analysis showed site, Borrmann classification, postoperative lymph node metastasis (pN), and metastasis in LN6 and LN9 were predictive factors for LN14v micrometastasis or metastasis (P < 0.05). The 5-year survival rate in the positive group (LN14v micrometastasis or metastasis) was 12.4%. The prognosis of patients without LN14v lymph node micrometastasis was better than that of the positive group, whereas the difference between group of LN14v micrometastasis and LN14v metastasis was not obvious. In matched analysis, patients with stage III gastric cancer L/M area, pN2-3 and LN6(+) underwent lymphadenectomy of LN14v had better survival than those without lymphadenectomy of LN14v. Conclusion: Lymph node micrometastasis may provide accurate prognostic information for patients with gastric cancer. Moreover, lymphadenectomy of LN14v might improve the survival of patients with stage III gastric cancer of L/M area, pN2-3 and LN6(+).